Development and Quality Enhancement of Fried Fish Cake Prototype with Transglutaminase, Trehalose, and Herbal Oil for Room Temperature Distribution - Ye Youl Kim; Khawaja Muhammad Imran Bashir; Seonyeong Kang; Yongjoon Park; Jae Hak Sohn; Jae-Suk Choi (Gels)
This study focuses on developing a fried fish cake prototype with improved quality and extended shelf-life, enabling room-temperature distribution through an innovative high-temperature and high-process retort method. Surimi-based products typically necessitate cold storage and a refrigerated distribution system, affecting their physical properties and flavor while escalating costs. By incorporating Transglutaminase (TGase), trehalose, and herbal oils, and optimizing the heating process using the response surface methodology, this research addresses challenges related to changes in physical properties, color, and off-flavors during high-temperature and high-pressure treatment. The addition of 0.37% ACTIVA-K TGase significantly enhanced gel strength by promoting protein cross-linking, while 0.75% trehalose improved color stability by suppressing browning, thus enhancing visual appeal. A 0.1% concentration of bay oil effectively enhanced the flavor profile by masking undesirable odors without compromising the sensory quality. Optimized processing conditions maximized DPPH radical scavenging activity, whiteness, and gel strength, ensuring superior product quality and safety. Nutritional analysis confirmed a balanced composition of moisture, protein, essential amino acids, and minerals, in accordance with Korean national standards for acid values. Microstructural examination revealed a uniform network structure, contributing to excellent texture and sensory evaluations. Shelf-life predictions indicated a storage duration of approximately 19 months, surpassing commercially available products and offering a competitive edge. This novel approach allows surimi-based products to be stored and distributed at room temperature, while also providing the potential for increased profitability.